2009
DOI: 10.1371/journal.pone.0007063
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Methanobrevibacter smithii and Methanosphaera stadtmanae Detected in the Human Gut Using an Improved DNA Detection Protocol

Abstract: BackgroundThe low and variable prevalence of Methanobrevibacter smithii and Methanosphaera stadtmanae DNA in human stool contrasts with the paramount role of these methanogenic Archaea in digestion processes. We hypothesized that this contrast is a consequence of the inefficiencies of current protocols for archaeon DNA extraction. We developed a new protocol for the extraction and PCR-based detection of M. smithii and M. stadtmanae DNA in human stool.Methodology/Principal FindingsStool specimens collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
300
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(319 citation statements)
references
References 28 publications
17
300
1
1
Order By: Relevance
“…Methanobrevibacter smithii and Methanosphaera stadtmanae (Methanobacteriales) are considered to be the prevalent methanogens in the human gut (59). In our study, sequences belonging to both species were identified in DGGE fingerprints from inlet wastewater samples and in pyrotag libraries from the first weeks of biofilm development, suggesting that archaeal colonizers at early stages of biofilm development derive from human fecal material in wastewater.…”
Section: Discussionmentioning
confidence: 56%
“…Methanobrevibacter smithii and Methanosphaera stadtmanae (Methanobacteriales) are considered to be the prevalent methanogens in the human gut (59). In our study, sequences belonging to both species were identified in DGGE fingerprints from inlet wastewater samples and in pyrotag libraries from the first weeks of biofilm development, suggesting that archaeal colonizers at early stages of biofilm development derive from human fecal material in wastewater.…”
Section: Discussionmentioning
confidence: 56%
“…The relative abundance of the mcrA gene also appeared to be stable and stayed at low levels (log10-4.82 ± 0.82 at day 1, log10-5.2 ± 0.26 at day 2, log10-5.15 ± 0.76 at day 4, log10-3.82±1.18 at day 8 and log10-4.93 ± 0.64 at day16) over the entire duration of the conventionalisation, suggesting that the methanogen population was among the early colonisers and had already reached its final population size early in the experiment. Although the relatively low absolute abundance of the mcrA gene may be an underestimation due to DNA isolation procedures that were not optimised for lysis of the methanogens (Dridi et al, 2009), the stability of the gene's abundance in the microbiota is most probably an accurate reflection of the evolution of this microbial group over time. In contrast, the dsr gene appeared to be B100-fold more abundant in the ecosystem during later stages of the conventionalisation (Figure 2a), increasing from Blog10-2.54 ± 0.2 during days 1-2 to log10-4.4±0.86 at days 4, 8 and 16 post-conventionalisation.…”
Section: Dynamic Establishment Of Microbial Communitiesmentioning
confidence: 99%
“…Results were expressed as the number of M. oralis cell/ml of specimen (Table 1). A quantification synthetic plasmid was used as an internal control to monitor PCR inhibition, and the total bacterial load was measured as previously described (11). The PCR program was 95°C for 5 min, followed by 40 cycles of 95°C for 1 s, 60°C for 35 s, and 45°C for 30 s. A calibration curve was done by measuring the cycle threshold (C T ) value of a serial dilution of M. oralis (10Eϩ01 to 10Eϩ09).…”
mentioning
confidence: 99%